Physiotherapy management in case of Post Reconstruction of anterior cruciate ligament sinistra at Sport clinic IBEST PHYSIO SOLO: Case Report - Dwiyanti, Neriza (UNIB Press, 2025)
The ACL is an important ligament in the knee that connects the femur to the tibia. anterior cruciate ligament injuries can result from a sudden knee injury in any direction resulting in partial or complete tearing of the ligament. Trauma can also cause anterior cruciate ligament tears, especially direct trauma to the knee due to lateral forces. The incidence of ACL injury in some European countries is around 29-32 cases per 100,000 people. This study is a descriptive case study involving one client with participatory observation method. Physiotherapy interventions include ice packs, TENS, and exercises given in the form of quadsets, straight raises, ankle sets, hamstring sets, gluts sets, and heel slides . The subjects were 27-year-old parahyangan soccer athletes with a height of 182 cm, a weight of 70 kg, and a BMI of 21.1 in the ideal category. The patient came to the IBESt PHYSIO SOLO physiotherapy clinic on August 20, 2023 with complaints of pain in the outer right knee. Physical examination showed normal results except pain examination using the numerical Rating Scale (NRS) obtained silent pain 2/10, tenderness 4/10, and motion pain 5/10. Postoperative ACL Diagnosis through X-ray dextra results. After physiotherapy with ice packs, TENS, and exercises given in the form of quadset, straight raise, ankle set, hamstring set, gluts set, and heel slide six times, obtained a significant reduction in pain and increased functional activity in post op ACL patients. Patients are advised to undergo regular physiotherapy, do stretching exercises before and after activities, and compress with warm water if they experience pain.